Representation and analysis of soccer players' actions using principal components - Barros, R. M. L.; Cunha, S. A.; Magalhaes, W. J.; Guimaraes, M. F. (Teviot Scientific Publications Ltd, 2006)
This paper proposes the use of the Principal Components Analysis (PCA) method to represent and to analyse soccer players' actions distribution in the pitch. The seven games of the Brazilian National Team during the 2002 World Cup were analysed. The player's position actions were measured from videotapes in a computer interface. The results were: a) the graphical representation, given by two orthogonal segments in the two directions of maximal variability and centred at the mean of each player's actions position; b) the eccentricity measurement, given by the variability ratio and c) the actions zone area, given by variability product. The results showed that the individual characteristics of acting were well represented by the PCA, allowing comparisons among games and providing insights related to the tactical organisation of the team.
Keywords: biomechanics; notation; tactical analysis